Mental health nurses’ experiences of caring for inpatients with severe mental disorders: a qualitative study - Roghaieh Keykha; Naima Seyedfatemi; Seyedeh Narjes Mousavizadeh; Parvaneh Vasli (BMC Psychiatry)
Abstract Background Patients with severe mental disorders (SMDs) often have complex needs that require long-term, multifaceted care. Exploring the experiences of mental health nurses (MHNs) in this context offers valuable insights into previously underexplored aspects of psychiatric care. The objective of the present study was to examine the experiences of MHNs in providing care for inpatients with SMDs in psychiatric wards in Iran. Methods This study used a qualitative research design based on conventional content analysis. The participants were 20 MHNs working in psychiatric wards in Iran, selected through purposive sampling. Data were collected through semi-structured, in-depth individual interviews, with a mean duration of 45 min. The data were then analyzed using conventional content analysis, with the help of MAXQDA (ver.10) software. Results The data analysis reduced to the emergence of three main themes and 12 categories, including (1) “care based on the nature of the disease”, comprised of four categories, viz., disease symptoms and specific nature, nursing care to prevent harm to oneself and others, therapeutic communication, and central role of medicinal care; (2) “patient- and family- based care”, with four categories of personalized care, trust building, respecting, understanding, and accepting patients, and family education; and (3) “complex and burdensome care”, containing four categories, i.e., challenges in gender-based care, challenges due to disease symptoms, psychological complications of care, and physical complications of care. Conclusion The study results clarified three main themes associated with MHNs’ experiences of caring for inpatients with SMDs. Healthcare managers and policymakers could in this way make use of these findings to improve MHNs’ performance in psychiatric wards and boost up the quality of nursing care for inpatients with such conditions. Clinical trial number Not applicable.